A Month in the Life of José Salud, Forester in the Spanish Philippines, July 1882. (1st January 2009) - Bankoff, Greg
Abstract : The discovery of a monthly work schedule for José Salud, a district forester on the island of Panay, provides us with an unique insight into the operations and workings of the Inspección general de Montes, the Spanish colonial forestry service in the Philippines. The records of this agency were mainly lost in fire and war but the fortuitous preservation of a personal report for July 1882 provides us with a tantalising glimpse into the operations and methods of forestry in the archipelago at that time. For one month, we are able to follow an assistant forester on his daily rounds about Capiz and in so doing come to realise how the forest was being transformed from a resource and a refuge into an arena where state management practices and indigenous customary rights competed alongside those who saw trees as nothing more than a commercial enterprise. This paper charts a social and environmental history of scientific forestry during the last decades of the nineteenth century through the lens of one man's activities. Rather than being separate inquiries, these two perspectives reinforce and complement one another, providing greater insight into both colonial social dynamics and the state of the environment.